PARADOXICAL REDUCTION IN PREVALENCE OF VIBRIO CHOLERAE IN ITS NICHE ENVIRONMENT - RUMPA SAHA; SHUKLA DAS; MAHESH WAGHMARE; V. G. RAMACHANDRAN (International Journal of Pharma and Bio Sciences, 2013)
Since 2007 incessantly for 3 years rise in Vibrio cholerae cases were suddenly seen to have fallen drastically since 2010. Fecal specimens were collected from 2745 patients with cholera like illness between 2007-2011 and subjected to culture followed by antimicrobial susceptibility testing of Vibrio cholerae isolates by Kirby Baur disc diffusion method. Of the 2745 samples examined, 11.04percent were positive for Vibrio cholerae. During 2007-2009, 242 cases were positive for V. cholerae with cresting in 2009 when 97 cases were reported as positive. However in 2011 it drastically declined to 22 cases. Resistance to nalidixic acid, furazolidone and co-trimoxazole was constantly high (100percent). While decline in resistance to drugs like gentamicin, tetracycline and ciprofloxacin was sensed, alongside, largely isolates remained susceptible to chloramphenicol. The development of multi-antibiotic resistance V.cholerae along with the decrease in number of cases made us ponder over the possibility of viable but non cultivable strains of V.cholerae. A dramatic reduction in the number of cholera in an endemic area, representing a derivation from the routine and not accompanied by an identifiable infrastructure transformation in the transmission high slum areas may point to the possibility of fundamental change in the biologic behaviour of the pathogen worthy of investigation. If trends in antimicrobial susceptibility can serve as a surrogate for this it would be an easy alternative to act as a sentinel to provide an in depth study.